Characterisation of dextran AP-27 produced by bee pollen isolate Lactobacillus kunkeei AP-27 - Yilmaz, Mustafa T.; Ispirli, Huemeyra; Alidrisi, Hassan; Taylan, Osman; Dertli, Enes (ELSEVIER SCI LTD, 2023)
An exopolysaccharide (EPS) produced by bee pollen isolate Lactobacillus kunkeei AP-27 was characterised in this study. EPS monomeric composition of strain AP-27 was characterised by High-performance liquid chromatography (HPLC) analysis and glucose was the only sugar in the EPS repeating unit. Structural analysis of glucan AP27 by H-1 and C-13 Nuclear magnetic resonance (NMR) analysis demonstrated that this glucan was a dextran ((1-*6)-linked alpha-D-glucose units as the main body) consisting very low level of (1-* 4)-linked alpha-D-glucose units (similar to 0.5 %). Dextran AP-27 had a degradation temperature of 308 degrees C that revealed its superior thermal strength identified by Thermogravimetric (TGA) and Differential scanning calorimetry (DSC) analysis. The molecular weight of dextran AP-27 was determined to be 25 kDa by Gel Permeation Chromatography (GPC) analysis. Crystallographic properties of dextran AP-27 was determined by X-ray diffraction (XRD) analysis that divulged its amorphous feature. Scanning Electron Microscopy (SEM) analysis was applied for microstructural characterisation of dextran AP-27 which revealed its regular sphere like characteristics. These findings suggest that Lactic Acid Bacteria (LAB) strains from different environments such as bee products can be the source for distinct EPS producer strains.
Keywords: Exopolysaccharides; Bee isolates; LAB; Lactobacillus kunkeei; Dextran; GLUCANSUCRASE; GLUCAN; ENZYMES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering